Stereotactic body radiotherapy for primary hepatic malignancies – Report of a phase I/II institutional study. Issue 1 (October 2016) - Weiner, Ashley A.; Olsen, Jeffrey; Ma, Daniel; Dyk, Pawel; DeWees, Todd; Myerson, Robert J.; Parikh, Parag
Abstract: Background and purpose: To report outcomes and toxicities of a single-institution phase I/II study of stereotactic body radiotherapy (SBRT) in the treatment of unresectable hepatocellular cancer (HCC) and intrahepatic cholangiocarcinoma (IHC). Materials and methods: Patients with Child-Pugh score less than 8 were eligible. A total of 32 lesions in 26 patients were treated with SBRT. Kaplan–Meier survival analysis was performed. Toxicities were graded by CTCAEv4 criteria and response was scored by EASL guidelines. Results: Median prescribed dose was 55 Gy (range 40–55 Gy) delivered in 5 fractions. Mean tumor diameter was 5.0 cm and mean GTV was 107 cc. Median follow-up was 8.8 months with a median survival of 11.1 months, and one-year overall survival was 45%. Overall response rate was 42% and one-year local control was 91%. Nine patients experienced a decline in Child-Pugh class following treatment, and two grade 5 hepatic failure toxicities occurred during study follow-up. Conclusions: Primary hepatic malignancies not amenable to surgical resection portend a poor prognosis, despite available treatment options. Though radiation-induced liver disease (RILD) is rare following SBRT, this study demonstrates a risk of hepatic failure despite adherence to protocol constraints.